A multi-criteria assessment for native forest policy analysis: the case of Caldén forest in the province of Córdoba, Argentina - Tello, Diego Sebastián; De Prada, Jorge Dante; Cristeche, Estela Raquel (Springer Nature, 2020)
The objective of this work is to develop a discrete multi-criteria model to evaluate dif-ferent Argentina. The application of the PROMETHEE multi-criteria method integrates a private cost–benefit analysis that describes the policy effects on farms and a contin-gent valuation study that describes the valuation of forest ecosystem services by the urban population of that region. The impact of five policy alternatives considering seven sustainability criteria was simulated. Criteria weighting was applied taking into account the preferences of theoretical decision-maker profiles and workshop participants. Our study finds that the most preferred alternatives are extension programs with and without prohibition of deforestation. The multi-criteria decision analysis shows an almost generalized coincidence, both in the simulation of theoretical weightings and in the workshop: The reforestation program with prohibition of deforestation is the best performance alternative, while deregulation is the alternative with the worst performance. Only when considering a free-market pro-file, deregulation has the best performance. It is concluded that multi-criteria methods facilitate the decision-making process, assessing policy alternatives by means of a wide range of criteria and by enabling different actors to express their preferences. Conse-quently, it constitutes a useful tool to support public decision making, particularly for policies related to the conservation of dry forests at local and global scales.